Hypercoagulability and Platelet Abnormalities in Inflammatory Bowel Disease - Senchenkova, Elena; Seifert, Hilary; Granger, D. Neil (Seminars in Thrombosis and Hemostasis, 2015)
Patients with inflammatory bowel disease (IBD) exhibit a threefold higher risk for development of systemic thrombosis than the general population. Although the underlying causes of the increased risk for thrombus development remain poorly understood, there is a large body of evidence suggesting that abnormalities in coagulation, fibrinolysis, and platelet function may contribute to this response. Changes in hemostatic biomarkers are consistent with subclinical activation of coagulation system, including tissue factor activation, impaired protein C pathway, enhanced thrombin generation, and diminished fibrinolytic capacity. There is also evidence for an increased production and reactivity of platelets, with an enhanced formation of platelet–platelet and platelet–leukocyte aggregates. The altered coagulation and platelet function, and the predisposition to thrombus formation have also been demonstrated in animal models of IBD. The animal studies have revealed a major role for inflammatory cytokines, including tumor necrosis factor-α, interleukin (IL)-1β, and IL-6, as mediators of the platelet abnormalities and enhanced thrombus development in experimental IBD. These findings in animal models raise hope for the development of novel therapeutic strategies to reduce thrombosis-related mortality in IBD patients.
Keywords: colitis; thrombocytosis; coagulation; fibrinolysis; platelet–leukocyte aggregation; interleukin-6